Analisis Komparatif Respons Dinamik Sistem Lintasan Kereta pada Track Lurus dan Melengkung Berbasis Simulasi Numerik - Agus Susanto; Hanum Arrosida; Wahyu Pribadi; Yorrys Firdausi (P3M Politeknik Negeri Cilacap, 2026)
The dynamic response of the wheel–rail–sleeper system is influenced by track geometry and operational parameters, particularly train speed. This study analyzes and compares the dynamic response of railway track systems on straight and curved tracks using a dynamic modeling and simulation approach. The system is represented as a multi-degree-of-freedom mass–spring–damper model capturing the interaction between wheel, rail, and sleeper. Simulations are conducted using the Runge-Kutta method at speeds of 20, 60, and 120 km/h. Analysis in both time and frequency domains is performed to identify vibration characteristics and resonance behavior. Results indicate that curved tracks produce higher vibration amplitudes due to centrifugal forces and uneven load distribution. The difference in spectral amplitude between straight and curved tracks remains small at 20 km/h, but increases significantly at 60 km/h and 120 km/h. At the highest speed, the wheel and rail amplitude on the curved track reaches 80 m/s² compared to 28 m/s² on the straight track, while the bearing amplitude increases from 1.1 m/s² to 3 m/s². These findings indicate that the influence of track geometry becomes more significant as train speed increases. Increasing speed significantly amplifies system response and leads to a tendency toward partial resonance at higher speeds. Moreover, frequency energy distribution becomes more complex, especially on curved tracks. These findings emphasize the importance of considering track geometry and speed in railway track design.